Predict of job performance and resiliency based on personality characteristics (Kurdistan University of Medical Sciences, 2016)
Introductionand Aim: personality trait determines the motivation and persons perspective regarding career and the way person responds to career demands. The present study was conducted to predict job performance and resiliency based on personality traits on the employees of Kermanshah Municipality. Materials and Methods: the study population consisted of all employees of Kermanshah municipality working at 1st, 2nd, and 3rd districts of Kermanshah in 2014 on 550 people. The sample of this study included 225 who were randomly selected using Morgan table. The instrument condisted of five factor personality questionnaire (NEO) Costa and McCrae (1985), Connor- Davidson resilience Scale questionnaire (2003) and Patersons job performance questionnaire (1989). Data analysis was done using statistical software SPSS16, LIDRL, descriptive statistics and inferential statistics tests including path ananlysis, correlation, regression analysis and independent T. Findings: The results showed that exogenous and extroversion variables had regression coefficient of 0.15 and 0.19 respectively and a direct significant effect on job performance. Moreover, there was a significant positive correlation between job performance and resiliency and there was no significant difference between male and female job performance. Conclusion: In order to improve the human resources, more attention should be paid to the role of personaliy factors and resilience in the equations of human resources.